EFECTO DEL SELENIO EN PLANTAS DE PIMIENTO (Capsicum annuum L.) BAJO CONDICIONES DE INVERNADERO - Benítez Salvador, Adriana Mariuxi (2023)
Pepper (Capsicum annuum L.) is a vegetable of great popularity worldwide due to its nutritional value. Selenium is a beneficial element for plants in low concentrations, it provides greater tolerance against biotic and abiotic stress, stimulating plant growth. The present research was carried out at the Campus “La María” of the Universidad Tecnica Estatal de Quevedo, with the objective of evaluating the effect of selenium on pepper plants (Capsicum annuum L.) under greenhouse conditions.